Analisis Faktor - Faktor Yang Mempengaruhi Tingkat Keuntungan Pada Koperasi Wanita An-Nisa Periode Tahun 2014-2019 - Topan Siswanto; Satriawan .; Riska Alfi Hikmatin (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2021)
This study aims to determine how the effect of working capital and accounts receivable turnover affects the level of profit, in this case the measurement uses the level of profitability. To measure capital and accounts receivable turnover, in this study researchers used multiple linear regression analysis approach. The object of this study is located in the AN-Nisa women's cooperative which is located in North Lombok district, West Nusa Tenggara Province. The data obtained at the research location are in the form of financial reports for 6 years, from 2014 to 2019. The results of this study indicate that the ability of the An-Nisa cooperative to obtain profits is mostly influenced by the variables used in this study, namely capital and accounts receivable turnover. So that the ability to manage capital and the better governance of providing accounts receivable will have a major impact on the level of profits obtained. This can be seen from the test results of the coefficient of determination, where the ability of capital and accounts receivable turnover have an impact on the profit level of 98.40 percent